Magnitude of clinical inertia and its associated factors among adult patients with asthma on chronic follow-up at Jimma Medical Center, Ethiopia: prospective observational study - Berhanu Teshome Derese; Abduba Guyo Wariyo (BMJ Open)
Objective To assess the magnitude of clinical inertia and its associated factors among adult patients with asthma on chronic follow-up at Jimma Medical Center, Ethiopia, from December 2021 to May 2022.Design and setting A hospital-based prospective observational study was conducted in Jimma Medical Center from 1 December 2021 to 30 May 2022.Participants 135 patients with asthma who fulfilled the inclusion criteria were enrolled in the study consecutively and followed for 3 months.Results Of 148 patients, 135 patients’ data were analysed. The mean (SD) age of the patients was 52.03 (±15.75) years. More than half (54.1%) of the study participants were men. Most of the study participants (68.9%) at the first and (70.4%) at the second visit, which is 3 months after the first visit, had clinical inertia, respectively. Comorbidity (adjusted OR (AOR) 3.35, 95% CI (1.15, 9.81), p<0.027), asthma duration of 5–10 years (AOR 7.58, 95% CI (1.51, 38.05), p<0.014), moderate persistent asthma (AOR 6.91, 95% CI (2.46, 19.42), p<0.00) and severe persistent asthma (AOR 10.84, 95% CI (1.1, 107.0), p<0.041) were contributing factors for clinical inertia.Conclusions The burden of clinical inertia in this study was high at both visits. Comorbidity, duration of asthma of 5–10 years, moderate persistent and severe persistent asthma were identified as contributing factors to clinical inertia. Policymaker intervention to avoid clinical inertia is necessary to improve asthma treatment outcomes.